Analisis Efektifitas Pajak Daerah Kabupaten Bojonegoro - Wahed, Mohammad; Ayu P, Indahning Sukma (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2022)
The purpose of this study was to determine the level of contribution and effectiveness of PBB-P2 tax, hotel tax and restaurant tax in an effort to increase local revenue (PAD) in Bojonegoro Regency through a quantitative approach. The analytical method used in this study is a statistical method to analyze the target and realization of taxes and local revenue. The data used in this research is secondary data from the Regional Revenue Agency (Bapenda) of Bojonegoro Regency. The results of this study found that: 1) the overall effectiveness of the PBB-P2 tax during the study period was categorized as very effective. This is in line with the contribution value of PBB-P2 tax which gives the largest contribution to Bojonegoro Regency's original revenue; 2) the same value also occurs in the effectiveness of hotel taxes during the research period which is categorized as very effective. However, this result is inversely proportional tothe value of the contribution from hotel taxes to Bojonegoro Regency's original revenue which is in the very small category; and 3) the level of effectiveness of the restaurant tax during the study period is also categorized as very effective. However, although the target and realization of the restaurant tax is very effective, this tax contributes very little to Bojonegoro Regency's original revenue.